Model Pengelolaan Dana Corporate Social Responsibility (CSR) untuk Keberlanjutan Lingkungan: Kajian Program Sedekah Sampah Digital PT. Indocement Tunggal Prakarsa Tbk - Wardono, Gadang; Ubaidilah, Muhamad; Susilowati, Endah; Wahyudi, Didu (Universitas Batanghari Jambi, 2024)
PT Indocement Tunggal Prakarsa Tbk, a leading producer in Indonesia, has implemented a new waste management program as part of its corporate social responsibility (CSR) and environmental sustainability efforts. This program utilizes a unique waste management model and a social-based waste management concept. The study employs a mixed-method approach, including both quantitative and qualitative methods, with data collected through questionnaires, focus group discussions, and field observations. The waste management system is digital, using the scrum method, making it easier to adapt to changing user needs. The digital platform facilitates waste management, distribution, and efficiency, ensuring transparency in waste management. The program also helps the company report total waste and waste management performance in real-time.